TEAD activity is restrained by MYC and stratifies human breast cancer subtypes. Issue 19 (1st October 2016) - Elster, Dana; Jaenicke, Laura A.; Eilers, Martin; von Eyss, Björn
ABSTRACT: c-Myc (MYC) is an oncogenic transcription factor that is commonly overexpressed in a wide variety of human tumors. In breast cancer, MYC has recently been linked to the triple-negative subtype, a subtype that lacks any targeted therapy. Previously, we demonstrated that MYC behaves as a potent repressor of YAP and TAZ, 2 transcriptional coactivators that function as downstream transducers of the Hippo pathway. In this previous study, MYC repressed YAP/TAZ not only in primary breast epithelial cells but also in mouse models of triple-negative tumors. Here, we extend our previous bioinformatic and experimental analyses and demonstrate that MYC deregulation in primary breast epithelial cells leads to a robust repression of TEAD transcription factor activity, the transcription factor family mainly responsible for YAP/TAZ recruitment. Surprisingly, we find that MYC and TEAD activity is able to stratify different breast cancer subtypes in large panels of breast cancer patients. Thus, a deep understanding of the MYC-YAP/TAZ circuitry might yield new insights into the establishment and maintenance of specific breast cancer subtypes.